Labor market trends and the need for reengineering higher education (Empresa y Sociedad, 2024)
The dynamics of the labor market have changed considerably and are currently experiencing a major shift. The skill levels that used to be enough in the workplace have become inadequate for the current workplace requirements. At least in the case of the United States, the kind of jobs that allowed work from home during the pandemic typically required college education; this may be a silver lining for colleges. Coupled with this, the admission test optional policies opened the doors of colleges for many otherwise disadvantaged students. The life cycle duration of technical skills has become shorter than ever before. Issues in innovation, demographic shifts, socio-cultural issues, aging population and technological advances are driving educators, employers, and policy makers to re-examine higher education to address the skill gaps currently existing in the workplace. This paper brainstorms some of these topics and propose solutions for policy makers.